2022
DOI: 10.21203/rs.3.rs-1236438/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naloxone’s displacement of [11C]carfentanil and duration of receptor occupancy in the rat brain: implications for opioid overdose reversal

Abstract: The continuous rise in opioid overdoses in the United States is predominantly driven by very potent synthetic opioids, mostly fentanyl and its derivatives (fentanyls). Although naloxone (NLX) has been shown to effectively reverse overdoses by conventional opioids, there may be a need for higher or repeated doses of NLX to revert overdoses from highly potent fentanyls. Here, we used positron emission tomography (PET) to assess NLX’s dose-dependence on both its rate of displacement of [11C]carfentanil ([11C]CFN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We first examined the effects of naloxone delivered subcutaneously at a relatively small, clinically relevant dose (0.2 mg/kg or 14 mg/70 kg) on brain oxygen responses induced by iv heroin (0.1 mg/kg) (92). At this dose, naloxone induces robust blockade of mu-opioid receptors (93). In our experiment, pre-treatment with naloxone fully blocked the biphasic effect of heroin (Figure 9A).…”
Section: Xylazine-heroin and Fentanylsupporting
confidence: 54%
“…We first examined the effects of naloxone delivered subcutaneously at a relatively small, clinically relevant dose (0.2 mg/kg or 14 mg/70 kg) on brain oxygen responses induced by iv heroin (0.1 mg/kg) (92). At this dose, naloxone induces robust blockade of mu-opioid receptors (93). In our experiment, pre-treatment with naloxone fully blocked the biphasic effect of heroin (Figure 9A).…”
Section: Xylazine-heroin and Fentanylsupporting
confidence: 54%
“…Fentanyl is associated with a profound increase in fatal overdose cases (Wilson et al, 2020). Naloxone (Narcan) is a MOR antagonist used clinically to reverse fentanyl's occupancy of brain MORs (Kang et al, 2022), reversing opioid overdose and precipitating opioid withdrawal (Kosten & Baxter, 2019;Rzasa Lynn & Galinkin, 2018). Recently, xylazine, an adrenergic α 2a receptor (A2aR) agonist sold as a veterinary anesthetic, has been increasingly detected in more fentanyl-positive urine screens and fentanyl overdose deaths (Nunez et al, 2021).…”
mentioning
confidence: 99%
“…Naloxone is rapidly eliminated and has a relatively short half-life of between 30 -120 min (21)(22)(23). A recent study showed that naloxone occupancy of MORs decreased from 90% occupancy 5 min after administration to 50% occupancy 20 min later, which demonstrated how short-lived naloxone's effects may be (24). Nalmefene, which is structurally similar to naloxone, has a much longer elimination half-life of approximately 11 hr in humans (25).…”
Section: Introductionmentioning
confidence: 99%